STUDENTS’ PERCEPTION ON THE EFFECTIVENESS OF USING YOUTUBE AS A MEDIA FOR LEARNING - Ayuni; Mukrim, Mukrim; Maf'ulah, Maf’ulah; Aminah, Aminah (Tadulako University, 2024)
This research aimed to discover students’ perception of using YouTube as a Media for Learning and factors that can contribute to the use of YouTube as a learning media. Qualitative descriptive are used. The subjects of this research were 30 students of class X 7. Questionnaires and interviews were applied to collect data. The questionnaire consists of 30 questions; interviews were conducted as supporting data. Based on data analysis, data from the questionnaire shows that most students agree with the use of YouTube as a medium for learning English. Learning to use YouTube also gives students new experiences in learning and can overcome boredom in monotonous learning. The interview results also showed that students were happy and gained new experiences by using YouTube as a learning medium. The conclusion can be drawn that students agree that using YouTube can overcome boredom in class, increase interest in learning and gain new experiences